A03 Genetic Modifiers Affecting The Age At Motor Onset In Huntington's Disease. (17th September 2014) - Jones, L; Gusella, JF; MacDonald, ME; Wheeler, V; Lee, J-M; Myers, RH; Latourelle, J; Jones, L; Harold, D; Holmans, P; Orth, M; Kwak, S
Abstract : Multiple biological mechanisms downstream of the expanded CAG repeat have been proposed to contribute to the pathogenesis of Huntington's disease (HD). Potential therapeutics aimed at many of these mechanisms have shown some benefits in models of disease, but none has yet translated to human HD. A critical issue is knowing which of the potential biological mechanisms alter the process that leads to manifest disease in people. About half of the variation in age at motor onset of HD is due to the length of the expanded CAG repeat in HTT, with the residual variation due both to other genetic and environmental factors. Identifying the genetic factors will give clues to the biological mechanisms capable of altering pathogenesis in HD. The GeM consortium has conducted a genome-wide association study (GWAS) to look for variants in the genome that are associated with age at motor onset. In total ˜1800 samples from the European Huntington's Disease Network Registry study and a similar number from the MGH HD research team were genotyped for 2.5 million single-nucleotide polymorphisms (SNPs). The GeM GWAS was combined with two other GWAS, giving a total of 4050 HD individuals with 40–55 CAG repeats. Analysis examined the association of SNPs with the difference between the age of motor onset predicted by the long CAG repeat and the actual age of motor onset. Variants at a locus on chromosome 15 containing several genes showed a genome-wide significant signal and several other regions showed consistent signals across the GWAS. We believe that these findings, from a large and well-powered study, provide insights into the pathways that are most likely to benefit patients if modified by drugs and validate them as targets for the design of rational therapies in HD.